2023
DOI: 10.1002/jmv.28781
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the late presentation and associated factors of people living with HIV in Turkey

Dilek Yildiz Sevgi,
Nazife Duygu Demirbas,
Irem Genc Yaman
et al.

Abstract: To identify the frequency of late presentation and late presentation with advanced disease, and associated factors in people living with HIV (PLHIV). Data from PLHIV diagnosed between 2008 and 2021 were retrospectively analyzed. Time of diagnosis (categorized based on key events affecting HIV care continuum e.g., national strategies, HIV guidelines, COVID-19 pandemic) and characteristics of late presenters (LP: CD4 ≤350 cells/mm³ or an AIDS defining event) and late presenters with advanced disease (LPAD: CD4 <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(180 reference statements)
0
1
0
Order By: Relevance
“…Other studies performed during a similar timeframe (2017 to 2020, 2019 to 2020 and 2015 to 2020) also revealed that male and older patients are at greater risk of late HIV presentation [ 23 , 24 , 25 ]. Additionally, other LP risk factors, including bisexual transmission, heterosexual transmission, being married, SSA origin, tuberculosis or hepatitis C virus coinfection, lower socioeconomic status and the fear of stigma, have been reported in various studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The discrepancies observed among those studies highlight the importance of identifying populations at risk of late presentation and developing specific guidelines according to the region.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies performed during a similar timeframe (2017 to 2020, 2019 to 2020 and 2015 to 2020) also revealed that male and older patients are at greater risk of late HIV presentation [ 23 , 24 , 25 ]. Additionally, other LP risk factors, including bisexual transmission, heterosexual transmission, being married, SSA origin, tuberculosis or hepatitis C virus coinfection, lower socioeconomic status and the fear of stigma, have been reported in various studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The discrepancies observed among those studies highlight the importance of identifying populations at risk of late presentation and developing specific guidelines according to the region.…”
Section: Discussionmentioning
confidence: 99%